2018
DOI: 10.14710/jitaa.43.2.149-158
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Assimilation of Saccharomyces cerevisiae B-18 isolated from gastrointestinal tract of Javanese duck

Abstract: This study had a purpose of obtaining potential indigenous yeasts for assimilating cholesterol and assessed the in vitro activity of Bile Salt Hydrolase (BSH) using Chloramphenicol Yeast Glucose (CYG) media supplemented CaCl2 and Taurodeoxycholic Acid (TDCA). Yeasts were collected from the gastrointestinal tract of Indonesian native chicken (Gallus javanicus), Javanese duck (Anas javanicus), and Muscovy duck (Anas moschata). The BSH assay was performed to determine secretion of BSH from yeast strain to conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
2
7
0
2
Order By: Relevance
“…It would be possible to deconjugate bile salt and might be effective in reducing serum cholesterol in poultry. In the previous study, isolates Lp AKK-30 and Sc B-8 showed lowering cholesterol activities (Julendra et al, 2017;Istiqomah et al, 2018).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…It would be possible to deconjugate bile salt and might be effective in reducing serum cholesterol in poultry. In the previous study, isolates Lp AKK-30 and Sc B-8 showed lowering cholesterol activities (Julendra et al, 2017;Istiqomah et al, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…In the previous study, S. cerevisiae has a potency to reduce cholesterol accumulation in the animal product (Istiqomah et al, 2018). Yeast positively interacts with bacteria by producing amino acids and vitamins for stimulating bacterial growth (Hatoum et al, 2012).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Fathi et al (2018) melaporkan bahwa suplementasi probiotik tidak meningkatkan kinerja produksi telur, akan tetapi dapat meningkatkan kualitas kulit telur. Dilaporkan oleh Istiqomah et al (2018) bahwa Saccharomyces cerevisiae berpotensi untuk mengasimilasi kolesterol in vitro.…”
Section: Pendahuluanunclassified
“…Saccharomyces spp juga ditemukan memiliki aktivitas hidrolitik garam empedu yang tinggi, yang bertanggung jawab untuk dekonjugasi garam empedu (Bidura dan Siti 2017). Menurut Istiqomah et al (2018) S. cerevisiae berpotensi untuk mengasimilasi kolesterol in vitro. Kolesterol plasma dan trigliserida berkurang pada ayam petelur yang diberi makanan yang dilengkapi dengan probiotik (Fathi et al, 2018).…”
Section: Hasil Dan Pembahasanunclassified